Accessibility, Usability, and Readiness Towards ICT Tools for Monitoring Educational Practice in Secondary Schools - H. O. Bolaji; Moses Adeleke Adeoye (Universitas Pendidikan Indonesia (UPI), 2022)
The accessibility, usability, and teachers' attitudes about using information and communication technology among secondary school teachers in the Ilorin Metropolis are investigated in this study. The research is a cross-sectional descriptive study. A total of 253 instructors (i.e. 179 from public and 74 from private schools; 123 males and 130 females) were chosen randomly from 2098 teachers in secondary schools in the Ilorin metropolitan using a random sample technique. The data for the study was collected using a specially constructed questionnaire. Three research questions were posed, and three of them were addressed. At the 0.05 level of significance, mean and standard deviation were employed to answer study questions. The study's findings revealed that most ICT facilities are inaccessible.